The Effect Advertising Attractiveness, Price Perception, And Electronic Word Of Mouth On Buying Interest (Survey On Consumers of managements students at Perjuangan University) - Nuraeni Mutiara Putri; Cece Rakhmat; Depy Muhamad Pauzy (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the partial and simultaneous effect of advertising attractiveness, price perception, and electronic word of mouth on Shopee users' buying interest in Management Study Program students Perjuangan University. The method used in this study is a quantitative method with a consumer survey approach with a sample of 100 respondents. The data collected is in the form of data which is carried out using a questionnaire technique. Analysis of the data used in this study using multiple linear regression analysis, correlation coefficient and coefficient of determination using SPSS version 26 software. The results show that advertising attractiveness, price perception and electronic word of mouth simultaneously and partially affect buying interest.